Simulation of Thermal Energy Storage Stratified Water Storage Tank for Solar Heating System - ahmad daud, amin faiq (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The past few decades have seen a steady increase in the use of solar water heaters in regions of the world that have a large amount of solar energy, however, since the sun can only provide energy for a fraction of every 24-hour sunshine. Cycle, there is a need to supplement solar water heaters with thermal energy storage systems. These systems use phase change materials (PCM) that can store additional energy to provide sufficient power, for example, to compensate for potential shortages that can arise from short production times, such as at night or on a very cloudy day. PCM can undergo solid to liquid phase transitions or conversion (that is melt cure) when heated to a temperature that is consistent with the heat input used. This study will explore ways to improve thermal efficiency in thermal water storage tanks by applying potential numerical modeling using PCMs containing Paraffin wax. Search for the most expedient PCMs for the finite element model, including the detection of changes in thermal conductivity and enthalpy at different temperatures. Elements that increase efficiency potentially include the use of encapsulated PCM for the spheres on the heat exchanger and changing the time required for the melt/cure process. This study also includes an overview of the Latent Thermal Energy Storage System (LHESS) and the theory behind it. The aim of this study is to developed and design a stratified storage water tank microencapsulate with PCM thermal energy storage. While other objectives are to simulate the thermal performance of the stratified water storage tank under varying hot water tank temperatures and to analyze the charging and discharging process of the encapsulated PCM used as a thermal insulator for the stratified storage water tank.